PENGARUH KELENGKAPAN FASILITAS KAPAL DAN KETEPATAN WAKTU TERHADAP KEPUASAN PENUMPANG KAPAL PT. MARINA LOGISTIK SEJAHTERA BALIKPAPAN (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Passenger satisfaction is the main goal in a business or business, especially sea transportation services. To achieve passenger satisfaction, of course, there are many important aspects that must be met by service providers. Aspects that must be met include the completeness of the ship's facilities and timeliness. The related variables in this study are the completeness of ship facilities and timeliness of passenger satisfaction on PT. Marina Logistik Sejahtera with multiple linear regression analysis method. All statements were tested with validity, reliability and had a correlation > 0.300 (valid) and had an alpha coefficient > 0.6 (reliable). From the calculation of the coefficient of determination, the value of Adjusted "R square" is 0.746 or 74.6% . It can be concluded that the completeness of ship facilities and timeliness have an effect of 74.6% on the satisfaction of ship passengers. The t test for the X1 variable shows that tcount > t table (6.709> 1.66071) with a sig value of (0.000 <0.05). In the t-test of the completeness of ship facilities and timeliness have an effect on satisfaction. ship passengers. While the results of the simultaneous test of the variables completeness of ship facilities and timeliness have a significant effect, it is proven that F count = 146.546 > f table = 1.77 by obtaining a sig value of (0.000 < 0.05) on ship passenger satisfaction, meaning that, the more complete ship and ship facilities are always on time making passengers feel satisfied using the transportation services provided by PT. Marina Logistik Sejahtera Balik